2003
DOI: 10.1074/jbc.m310053200
|View full text |Cite
|
Sign up to set email alerts
|

Insig-dependent Ubiquitination and Degradation of Mammalian 3-Hydroxy-3-methylglutaryl-CoA Reductase Stimulated by Sterols and Geranylgeraniol

Abstract: The endoplasmic reticulum enzyme 3-hydroxy-3-methylglutaryl-CoA reductase produces mevalonate, which is converted to sterols and to other products, including geranylgeraniol groups attached to proteins. The enzyme is known to be ubiquitinated and rapidly degraded when sterols and nonsterol end products of mevalonate metabolism accumulate in cells. Here, we use RNA interference to show that sterol-accelerated ubiquitination of reductase requires Insig-1 and Insig-2, membrane-bound proteins of the endoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
373
3
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 272 publications
(396 citation statements)
references
References 44 publications
17
373
3
3
Order By: Relevance
“…Despite its poor release and deglycosylation (Figure 5Ai, lanes 3 and 4), the dislocated HMG 350 -HA (YIYF3 AIAF) that was associated with Insig-1-Myc was predominantly un/deglycosylated, similar to the wild-type protein (Figure 5Bi, lanes 1-4). Radioactive pulse-chase experiments confirmed that the turnover of HMG 350 -HA (YIYF3 AIAF) mutant was not regulated by sterols (data not shown).A mutant HMG 350 -HA in which lysines 89 and 248 were replaced by arginines does not undergo sterol-regulated polyubiquitination and degradation (Sever et al, 2003a;Doolman et al, 2004). In response to sterols, the amounts of HMG 350 -HA (K89ϩ248R) that were released to the supernatant and pulled down along with Insig-1-Myc did not increase but were even slightly reduced ( Figure 5, Ai and Bi, lanes 5 and 6).…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…Despite its poor release and deglycosylation (Figure 5Ai, lanes 3 and 4), the dislocated HMG 350 -HA (YIYF3 AIAF) that was associated with Insig-1-Myc was predominantly un/deglycosylated, similar to the wild-type protein (Figure 5Bi, lanes 1-4). Radioactive pulse-chase experiments confirmed that the turnover of HMG 350 -HA (YIYF3 AIAF) mutant was not regulated by sterols (data not shown).A mutant HMG 350 -HA in which lysines 89 and 248 were replaced by arginines does not undergo sterol-regulated polyubiquitination and degradation (Sever et al, 2003a;Doolman et al, 2004). In response to sterols, the amounts of HMG 350 -HA (K89ϩ248R) that were released to the supernatant and pulled down along with Insig-1-Myc did not increase but were even slightly reduced ( Figure 5, Ai and Bi, lanes 5 and 6).…”
mentioning
confidence: 49%
“…A mutant HMG 350 -HA in which lysines 89 and 248 were replaced by arginines does not undergo sterol-regulated polyubiquitination and degradation (Sever et al, 2003a;Doolman et al, 2004). In response to sterols, the amounts of HMG 350 -HA (K89ϩ248R) that were released to the supernatant and pulled down along with Insig-1-Myc did not increase but were even slightly reduced ( Figure 5, Ai and Bi, lanes 5 and 6).…”
Section: Interaction Of Insig-1-myc With Hmg 350 -Ha: Effects Of Mutamentioning
confidence: 91%
“…Besides its role in ensuring protein quality, ERAD also has the capability to respond to the physiological requirement of mature proteins that transit or reside within the ER to regulate their homeostasis accordingly. This is well described for the negative feedback regulation of sterol biosynthesis, where abundant sterol metabolites induce ERAD‐mediated degradation of sterol biosynthetic enzymes like 3‐hydroxy‐3‐methylglutaryl‐coenzyme‐A reductase (HMGCR) (Gil et al , 1985; Sever et al , 2003) and squalene monooxygenase (SQLE) (Gill et al , 2011; Foresti et al , 2013). Beyond this pathway, only a few other substrates have been identified for regulatory ERAD.…”
Section: Discussionmentioning
confidence: 99%
“…Since ERAD‐dependent quality control has been linked to a range of cellular processes and human diseases (Zettl et al , 2011; Guerriero & Brodsky, 2012; Perrody et al , 2016), understanding its molecular mechanisms is an important step to develop potential treatment strategies (Tsai & Weissman, 2010; Hetz et al , 2013). In addition to its role in protein quality control of nascent polypeptides, ERAD has been implicated in regulating the abundance of mature proteins in response to changes in physiological conditions (Wiertz et al , 1996a,b; Sever et al , 2003; Brodsky & Fisher, 2008; Adle et al , 2009; Foresti et al , 2013; Avci et al , 2014; van den Boomen et al , 2014). However, only a few regulatory ERAD substrates have been described so far.…”
Section: Introductionmentioning
confidence: 99%
“…This pathway is activated when sterols and nonsterol end products of mevalonate metabolism accumulate in cells. Sterol-accelerated ubiquitination of HMG-CoA reductase requires Insig-1 and Insig-2; membrane-bound proteins of the ER (Sever et al 2003). Recently, it has been elegantly demonstrated that dtocotrienol stimulates the ubiquitination and degradation of HMG-CoA reductase and blocks processing of SREBPs, another sterol-mediated action of Insigs.…”
Section: Lipid-lowering Property Of Tocotrienols In Cardioprotectionmentioning
confidence: 99%